Integrative Analysis Reveals the Landscape of Hypoxia-Inducible Factor (HIF) Family Genes in Pan-Cancer. (25th November 2020) - Yang, Qian-Kun; Wang, Xue-Xin; Wang, Yang; Ni, Ni
Abstract : Inside the cancer microenvironment, reduced O2 concentration, termed as hypoxia, is a common phenotype and leads to cancer progression. However, little is known about how and when those HIF members are dysregulated in distinct cancers. Here, by integrating a full range of data of thousands of patients, we comprehensively analyzed the genetics, epigenetics, and transcriptomic level of HIF genes and further defined pathways triggered by disrupted hypoxia-inducible factors. We reveal the expression landscape of HIF family genes and further demonstrate that copy number variations underlie such dysregulation. Further analysis indicates that HIF genes associate with cancer hallmarks such as cell cycle and DNA damage response. Drug resistance analysis showed that HIF globally impacts drug effectiveness such as docetaxel. In summary, the overall analysis reveals the landscape of HIF genes in pan-cancer and may assist mechanism research about hypoxia.